2012
DOI: 10.1103/physrevb.86.054442
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of ultrafast laser-induced demagnetization in GdxFe100xyCo

Abstract: Laser-induced ultrafast demagnetization in ferrimagnetic Gd x Fe 100−x−y Co y thin films was studied experimentally as a function of Gd concentration (x = 18, 22, 24, 30%, and y ≈ 9-10%), pump fluence, and sample temperature. The results showed that the conditions for full demagnetization at the ultrafast time scale in Gd x Fe 100−x−y Co y thin metal films are easily achieved below the magnetization compensation point (T M ) and, furthermore, when the ratio between Gd and Fe concentrations is not too large. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 29 publications
3
26
5
1
Order By: Relevance
“…2(b). The AOS fluence switching window is thus reduced above T M , and this asymmetry of the switching window around T M is consistent with the literature [13][14][15]. Part of this effect might be attributed to the proximity with the Curie temperature T C .…”
Section: B Time-resolved Dynamics Around T Msupporting
confidence: 90%
See 1 more Smart Citation
“…2(b). The AOS fluence switching window is thus reduced above T M , and this asymmetry of the switching window around T M is consistent with the literature [13][14][15]. Part of this effect might be attributed to the proximity with the Curie temperature T C .…”
Section: B Time-resolved Dynamics Around T Msupporting
confidence: 90%
“…Among these, the exact role played by the magnetization compensation temperature T M at which the magnetizations of the two sublattices cancel each other out remains a puzzle. On the one hand, strong changes in the magnetization dynamics upon crossing T M have been observed [13][14][15], and AOS seems to occur preferably for alloys displaying a T M that can be reached through laser excitation [9,10,16]. On the other hand, atomistic simulations of the spin dynamics as well as experiments have shown that AOS is feasible below and above T M [6].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, it has been suggested, based on the studies of the ultrafast laser-induced demagnetization in GdFeCo alloys, that the angular momentum transfer from TM to RE sublattice plays an important role in the process. 40 Spatiallyand element-resolved studies of the reversal dynamics in GeFeCo have shown that there is the angular momentum transfer between Gd-rich and Fe-rich nanoscale areas in the GdFeCo sample which accompanies the reversal. 41 Recently, has been reported that there is a transfer of the angular momentum between RE and TM sublattices of the metallic ferrimagnetic alloys CoGd and CoTb induced by the action of the laser pulse and monitored by the spin-and orbital-resolved X-ray technique.…”
Section: Magnetization Reversal Induced By a Femtosecond Laser Pmentioning
confidence: 99%
“…The present experimental geometry at room temperature avoids laserinduced magnetization precessions 18 as well as laser-induced switching across a ferrimagnetic compensation point. [19][20][21] Rather, we are sensitive to the out-of-plane magnetization change as a result of laser-induced heating. Note that in the experiment, the magneto-optical signal of GdCo(Fe) comes mainly from the Co(Fe) 3d moments.…”
mentioning
confidence: 99%